Size-dependent mortality in a Neotropical savanna tree: The role of height-related adjustments in hydraulic architecture and carbon allocation - Zhang, Yong Jiang (2009)
Size-related changes in hydraulic architecture, carbon allocation and gas exchange of Sclerolobium paniculatum (Leguminosae), a dominant tree species in Neotropical savannas of central Brazil (Cerrado), were investigated to assess their potential role in the dieback of tall individuals. Trees greater than ∼6-m-tall exhibited more branch damage, larger numbers of dead individuals, higher wood density, greater leaf mass per area, lower leaf area to sapwood area ratio (LA/SA), lower stomatal conductance and lower net CO2 assimilation than small trees. Stem-specific hydraulic conductivity decreased, while leaf-specific hydraulic conductivity remained nearly constant, with increasing tree size because of lower LA/SA in larger trees. Leaves were substantially more vulnerable to embolism than stems. Large trees had lower maximum leaf hydraulic conductance (Kleaf) than small trees and all tree sizes exhibited lower Kleaf at midday than at dawn. These size-related adjustments in hydraulic architecture and carbon allocation apparently incurred a large physiological cost: large trees received a lower return in carbon gain from their investment in stem and leaf biomass compared with small trees. Additionally, large trees may experience more severe water deficits in dry years due to lower capacity for buffering the effects of hydraulic path-length and soil water deficits.